The Paradox of Immersive Artificial Intelligence (AI) in Luxury Hospitality - Gonçalves, Ana Rita (2024)
Gonçalves, A. R., Pinto, D. C., Shuqair, S., Mattila, A., & Imanbay, A. (2024). The Paradox of Immersive Artificial Intelligence (AI) in Luxury Hospitality: How Immersive AI Shapes Consumer Differentiation and Luxury Value. International Journal of Contemporary Hospitality Management, 36(11), 3865-3888. Article 24. https://doi.org/10.1108/IJCHM-11-2023-1689 --- %ABS3% ---This work received partial support from national funds through FCT (Fundação para a Ciência e a Tecnologia), under the projects –UIDB/04152/2020 and DSAIPA/DS/0113/2019– Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.